The influence of context : social movements, knowledge, and social change : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Sociology at Massey University - Denton, J. A. Margaret (Massey University, 1999)
Sociological approaches to social movements are discussed. I argue that the unintended consequences of social movement activity tend to be ignored. Social movement activity often exacerbates existing social divisions, and how this happens is not explained. I argue that this exacerbation is a consequence of divergent understandings, where it is not simply the case that one side of the conflict is 'right' and another 'wrong'. I examine debates in quantum physics, feminist epistemology, the sociology of scientific knowledge and ecocentric sociology for insights into how such differences in understandings arise. I find four different ways in which knowledge is shaped: through our ongoing socialisation, through the particular experiences that we draw on (observe) to form that knowledge, through physiological processes, and through being shaped for an end use. To take the influence of these contexts into account we need to maintain a distinction between reality and preterreality, and between noumena and phenomena. I argue for an evolutionary approach to understanding the ongoing mutual influence between our experiences and our understandings. I draw on Durkheim's theorisation of the emergence of understandings from social categories and recent work in the sociology of emotions to develop an understanding of the ongoing processes of mutual inherence that constitutes our identity in relationship to our social experience. I argue that the social does not exist as noumena; yet our understandings usually assume that it does. The social exists in the phenomena we experience, and is increasingly stabilised by socialised noumena as our shared understandings diverge. Social movements enable understandings to emerge from the social experience of the movement; but people outside the movement do not share that experience. Any understanding is not readily grasped by people who have not had congruent social experiences. Being exposed to social movement understandings will then mean that the ideas and experiences that were not congruent will be revisited and so reinforced. When social movement insights are enforced through regulative fiat the social situation can diverge further by introducing new forms of closure. I examine some ways in which this has occurred in public sector reforms in New Zealand. I suggest a way in which social movements can act to avoid this, by developing social movement sacraments that align processes of mutual inherence with social movement objectives.
Keywords: Social movements; Social change; Sociology of knowledge; New Zealand